AL-TAFĀ’UL AL-IJTIMĀ‘Ī LI AL-ṬĀLIBĀT AL-MUNTAQIBĀT FĪ AL-JĀMI‘ĀT AL-ISLĀMĪYAH AL-ḤUKŪMĪYAH FĪ MUQĀṬA‘AT BENGKULU (State Islamic University (UIN) of Sunan Ampel Surabaya, 2022)
This study explores the interaction of veiled students, the perceptions of students and lecturers towards them, and the influence of negative stereotypes that circulate on veiled students. The phenomenological approach used in this research is part of qualitative research. Participants are students from the State Islamic Institute of Curup and State Islamic Institute of Bengkulu. Data are analysed, using semantic reduction carried out by identifying important statements from the results of interviews, determining discussion themes, and describing the importance of the entire experience of veiled female students. The results show that the association of veiled students with students and lecturers at Islamic Higher Education of Bengkulu tends to go well and takes place normally. Students' perceptions of veiled students tend to be negative, considering veiling an excessive attitude in dressing. The effect of negative stereotypes on veiled students is that in general it does not affect the decision to veil among students.